Pope, interrupted. A qualitative study on memes, hashtags, and speech chains - Avelar, Marcus Vinicius (Texto Livre, 2015)
ABSTRACT: This article investigates the reaction, on Twitter, to Pope Benedict XVI’s resignation announcement. Specifically, this is a qualitative study in linguistic anthropology of how memes and hashtags circulated on Twitter between the day of the announcement of said resignation and the Pope’s last day in office, and identifies the speech chains created by them. The analysis of the corpus showed that Twitter users' deployment of hashtags serves two purposes: on the one hand, it creates a topic/comment structure that is later reproduced, modified or abandoned by other users. On the other hand, hashtags function as performative acts that create online ad hoc communities. In addition, this article also claims that English and Romance-language users created and circulated image and text-based memes differently, thus establishing two language-based speech chains. In sum, this article contributes to discussions on informational flux on online platforms by demonstrating that said flux does have constraints, and that those constraints are related to language-based communities of practice.KEYWORDS: Twitter. Speech chains. Hashtags. Memes.  RESUMO: O presente trabalho investiga a reação, no Twitter, ao anúncio da renúncia do Papa Benedito XVI. Trata-se de um estudo qualitativo, em antropologia linguística, de como memes e hashtags circularam no Twitter entre o anúncio da renúncia e o último dia de trabalho do Papa, com o objetivo de identificar as cadeias de fala criadas por estes memes e hashtags. A análise do corpus mostrou que emprego de hashtags pelos usuários do Twitter serve a dois propósitos: por um lado, cria-se uma estrutura tópico-comentário que é, depois, reproduzida, modificada ou abandonada por outros usuários. Por outro lado, as hashtags funcionam como enunciados performativos que criam comunidades online. Ademais, o presente artigo também afirma que usuários de língua inglesa e de línguas românicas criaram e circularam memes baseados em imagens e textos de maneiras distintas, estabelecendo, consequentemente, duas cadeias de fala baseadas nas suas respectivas línguas. Em resumo, este artigo contribui para as discussões sobre o fluxo informacional em plataformas online, ao demonstrar que há restrições a esse fluxo e que tais restrições estão relacionadas às línguas das diferentes comunidades de prática.PALAVRAS-CHAVE: Twitter. Cadeias de fala. Hashtags.Memes.